An improved robust EKF algorithm based on sigma points for UWB and foot-mounted IMU fusion positioning. Issue 2 (4th May 2021) - Wang, Yan; Li, Xin
ABSTRACT: The UWB-based positioning system can not provide high accuracy positioning result in NLOS conditions. The standard EKF or robust EKF algorithm is usually adopted to fusion IMU and UWB information, but it also has no enough accuracy in strong NLOS environment. A method based on sigma point sampling is proposed in this paper, in which the priori information and UWB observation are used to adjust the observation covariance. The experimental results show that the accuracy of the proposed method is improved by more than 66% and 50% compared to that of the standard EKF algorithm and the robust EKF algorithm respectively.